Dynamic measurements of Li depth profiles in a Li‐ion battery system under charging condition by means of ERD and RBS techniques. (7th August 2014) - Tsuchiya, Bun; Morita, Kenji; Nagata, Shinji; Kato, Takehisa; Iriyama, Yasutoshi; Tsuchida, Hidetsugu; Majima, Takuya; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> Depth profiles of Li in a Li‐ion battery system of Au/LiCoO2/LATP/Pt (LATP:Li1+X+YAlYTi2−YGeXP3−XO12) have been in situ measured at several stages of charging by means of the elastic recoil detection (ERD) and Rutherford backscattering (RBS) techniques with 9 MeV O4+ ion beam. The thicknesses of LiCoO2 and Au are estimated from the RBS spectrum for the as‐received specimen to be 190 and 27 nm, respectively. From the ERD spectrum, it is also found that there exists impurity hydrogen of ~5% in LiCoO2. Moreover, it is found from the ERD data analysis after the first charging of 0.48 × 1016 e/cm2 to Au electrode that the fractional concentration of Li in LiCoO2 at the interface with Au electrode steeply decreases to 0.8, recovers with depth toward the interface with LATP and attains at 1.3 above the original value. With increasing the amount of charge supplied, the slope in the Li composition from Au electrode to LATP increases gradually. The data on the charging is concluded to include the irradiation effects due to the incident O ions, since the data on a non‐irradiated part of the specimen obtained after finish of the charging shows that Li is almost completely reduced from LiCoO2. The dynamics of Li composition in LiCoO2 as a function of charging supplied is discussed in connection with hydrogen impurity and irradiation effect of the incident O ions. Copyright © 2014 John Wiley & Sons, Ltd.